A percepção dos agricultores em relação ao uso de agrotóxicos e sementes transgênicas - Santos, Gislaine Bergamo dos (2018)
This research reveals the risks of pesticides and GMOs used in Lines are José e Souza Naves, rural communities located in the West of Paraná. The objective of this study was to diagnose the use of agrochemicals and GMOs, and studying the farmers ' perception about the risks of your use. The methodology used was qualiquantitative, by means of a semi-structured form, applied to all residents of two rural communities of the municipality of four bridges-PR, representing a 74 sample farmers. The results showed that farmers in your entirety, used in agricultural production: glyphosate, Paraquat, 2.4 D, high toxicity pesticides the human body and high danger for the environment. In relation to the time of exposure to pesticides 81% of farmers are between 15 to 25 years. It was noticed that 59% of cases declared occurrence of changes in the body, including behavioural changes; 53% seek attendance by the health plan; 93% made acquisition of pesticides and transgenic seeds in cooperatives. It is concluded that the pesticides and GMOs are a threat to the sustainability of rural development, by affecting the health of farmers and the environmental balance. Emphasized the need to expand public and private policies on environmental education and care for people and the environment. Indicates need for adequacy of the public health services, encouraging disease prevention and the improvement of the medical diagnosis and nursing routines.